Rikitake dynamo system, its circuit simulation and chaotic synchronization via quasi-sliding mode control - Yi-You Hou; Cheng-Shun Fang; Chang-Hua Lien; Sundarapandian Vaidyanathan; Aceng Sambas; Mustafa Mamat; Muhamad Deni Johansyah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Rikitake dynamo system (1958) is a famous two-disk dynamo model that is capable of executing nonlinear chaotic oscillations similar to the chaotic oscillations as revealed by palaeomagnetic study. First, we detail the Rikitake dynamo system, its signal plots and important dynamic properties. Then a circuit design using Multisim is carried out for the Rikitake dynamo system. New synchronous quasi-sliding mode control (QSMC) for Rikitake chaotic system is studied in this paper. Furthermore, the selection on switching surface and the existence of QSMC scheme is also designed in this paper. The efficiency of the QSMC scheme is illustrated with MATLAB plots.